Perceptions of the use of mobile phones to access reproductive health care services in Tamale, Ghana - Agbenyo, John Stephen; Nzengya, Daniel M.; Mwangi, Suleiman Kairu (Frontiers in Public Health, 2022)
Introduction Africa has one of the world's highest populations of young people. In addition, Africa has one of the highest proportions of young people facing the worst health challenges. Although previous scholars have reported that young people were using mobile phones to fill in the gaps in accessing reproductive health services, among other health services, there was little comprehensive research on the perception of young people in Tamale, Ghana, on the use of mobile phones to access reproductive health services. This study analyzed the perceptions on mobile phone use to access reproductive health services among young people in Tamale, Ghana. Methods The research used a quantitative method design from a target population of 72,706 young people from selected peri-urban, low-income, middle income and high-income residential areas in Tamale Metropolis, Ghana. The sample size used was 397 young people. Participants were selected using a stratified multistage sampling strategy. Descriptive statistics were used to analyse the data. Results A total of 86% of the respondents agree that the use of mobile phones helps to overcome cultural challenges that young people in Tamale encounter in accessing reproductive health care. Also, 84.6% of the respondents agree that the use of mobile phones helps them to overcome inadequate access to reproductive health information and services. The use of mobile phones helps to overcome the negative attitude of health providers toward young people in need of reproductive health services was agreed by most of the respondents [strongly agree (35.4%) and agree (49.4%)]. Conclusion This study informed highly positive perceptions and attitudes toward the use of mobile phones to access Reproductive Health Services in Tamale, Ghana. There is, therefore the need for the health sector to reform its mode of prescriptions of medication, consultation, and service delivery to leverage on the advantages that mHealth presents.